The costs and benefits of hosting colonial sociable weaver nests for arid zone savanna trees - Aikins, Khan Timothy (Department of Biological Sciences, 2024)
The savanna ecosystem is water and, in some instances, nutrient-limited, creating competition among species. Species, however, coexist in this ecosystem through processing like facilitation acting together with competition. Facilitation is an ecological interaction in which one species enhances the habitat of another species. Research on facilitative interactions between birds and plants has mainly focused on pollination and seed dispersal, but many birds interact closely with plants at the nesting site during breeding or even year round for nesting and roosting. These interactions are not always reciprocally beneficial, but with costs and benefits that change in spatio-temporal contexts, especially in resource-constrained arid zone environments. The overall impacts of bird nesting, especially colonial species, on the growth and reproduction of host trees can be large, with these interactions potentially being crucial components of ecosystems. Overall, understanding the nature of the interactions between host trees and nesting birds may provide key information on understanding the life history of species and their communities. I, therefore, test the hypothesis that the interactions between animals and plants in the savanna ecosystem enhance the islands of fertility created by trees, which influences the growth and survival of vegetation in the environment. I used the interaction between sociable weavers (Philetairus socius) and their host trees (camelthorn Vachellia erioloba and shepherd Boscia albitrunca) to test this hypothesis. I predicted that trees that host the sociable weaver nest would have benefits and costs in the interaction, influencing the growth and reproduction of host trees differently from trees without a nest. I found that soils under trees without nests were characterized by higher N (2.3-fold) and P (1.3-fold) compared to grassland areas. However, I found that soils under nest trees had even higher concentrations of N (3.5-fold) and P (4.1-fold) than soils under trees without nests. Therefore, nest trees and trees without nests create islands of fertility, but nests accentuate nutrient accumulation. Soil C and N increased with increasing tree size and colony size. Seedling growth was significantly greater in the soils from islands of fertility that were accentuated by weaver nest presence. Seedlings grown in soils from bird islands of fertility showed more growth in shoots, while seedlings in grasslands showed more growth in roots, and lastly, tree islands of fertility were intermediate in both. There was significantly greater mean seedling height (1.4-fold) and the number of leaves (1.4-fold) in soils from bird islands of fertility than in both tree islands of fertility and grassland sites. The foliar nutrient stoichiometries of seedlings grown on nest-accentuated islands of fertility were similar to the stoichiometric ratios in soils from bird islands of fertility, showing that the faecal input of the sociable weaver accounts for the growth differences in these islands of fertility. The benefits for trees that host sociable weaver nests include higher foliar N, P, K, and Ca. Trees hosting nests did not show differences in seed weight, number of seeds per pod and pod weight. Seed nutrients did not vary substantially between trees with and without a nest. Seed germination and emergence did not differ between trees with and without a nest. There was, however, significantly shorter seed germination and emergence time in seeds infested with beetles than in seeds with no beetle infestation. The costs of hosting a sociable weaver nest include lower soil water infiltration rates under nest trees with larger colony sizes, which limits seed germination, despite good seed banks and nutrient-rich soils. There was also an average of 30% reduction in the photosynthetic area of nest trees, significantly more and larger branch fall in nest trees, and a mean of 39% dead terminal nest branches. The rate of dieback in trees was higher (ca. 6-fold) for nest trees than for trees without a nest. Trees with nests have significantly greater damage from beetles to the seeds (50% infestation) than trees without nests (34% infestation). Beetle-infested seeds in nest trees had a significantly high percentage of seeds that failed to emerge after germination than beetle-infested seeds in control trees. The ecological engineering activities of sociable weavers address the limitations of nutrients for the growth of the host tree in an arid zone savanna, but there is also a growth and reproductive cost for the host trees. The biotic interaction between sociable weavers and their host trees facilitates the survival of host trees in the resource-constrained arid zone savanna environment. In this interaction, there are growth costs to hosting the nest, but there were no substantial reproductive costs to host trees except for a high beetle infestation of host seeds. These combinations of feedback also establish the camelthorn and shepherd trees as powerful ecosystem engineers. The study also contributes to the literature on ecological engineering, showing how the association between the sociable weavers and savanna trees ameliorate conditions in N-limited desert soils which drives the growth of plants in this soil condition.